Influence of Air Cooling Jets on the Steady-State Shape of Strips in Hot Dip Galvanizing Lines∗. Issue 17 (2015) - Saxinger, M.; Steinboeck, A.; Baumgart, M.; Kerschbaummayr, P.; Kugi, A.
Abstract: The influence of air cooling jets on the steady-state shape of the strip in hot dip galvanizing lines is investigated. For this purpose, the force characteristic of a single nozzle is measured by a laboratory flow simulator. This approach differs from conventional methods, where typically, CFD simulations are used. Based on the air cooler force characteristic the stability of the equilibrium points is investigated and the influence of different types of boundary conditions, tensile loads, strip thicknesses, and cooler fan speeds is examined.